Strawberry Freshness Assessment by Hyperspectral Imaging - Georgiy V. Nesterov; Anastasia V. Guryleva; Milana O. Sharikova; Svetlana A. Sukhanova; Alexander S. Machikhin (Siberian Journal of Life Sciences and Agriculture)
Background. Strawberry is a highly valued and perishable food item. The freshness of these fruits plays a crucial role in their quality, as it determines their shelf life, nutritional content, visual appeal, and safety for human consumption. Traditional methods of assessing fruit freshness are subjective, labor-intensive, and have low productivity. This study aims to develop a methodology for quantitatively assessing the freshness of strawberries using hyperspectral imaging, which can provide objective and accurate measurements of fruit quality.